Analisis Defect Produk Cover Rear Center pada Mesin Injection Molding Menggunakan Metode FMEA di PT Remot Speed - Arrazzaq, Cavan Rijal; Hanifi, Rizal; Khamanie, Ayattulah Ali (Industrika : Jurnal Ilmiah Teknik Industri, 2026)
This study aims to analyze the types of defects found in the Cover Rear Center product manufactured using injection molding machines at PT. Remot Speed. Product defects such as flow lines, sink marks, burn marks, short shots, and discoloration can increase production costs, delay processing time, and reduce product quality. The Failure Mode and Effect Analysis (FMEA) method is used to identify potential causes of failure and determine corrective priorities based on the Risk Priority Number (RPN) calculation. Data were obtained through direct observation, operator interviews, and production documentation. Each defect type was analyzed using three main parameters: Severity (S), Occurrence (O), and Detection (D). The results show that flow lines have the highest RPN value of 200, making it the top priority for corrective action. The main causes include low injection speed, improper material temperature, and suboptimal mold design. Recommended corrective actions include adjusting process parameters such as increasing pressure, temperature, and holding time, as well as cleaning machine components. The application of FMEA proves effective in providing a structured overview of potential failures and appropriate improvement strategies. By implementing this approach, the company can reduce defect rates and enhance both product quality and production efficiency. Keywords: Cover Rear Center, FMEA, Injection Molding, Product Defect, Risk Priority Number